2021
DOI: 10.1007/s10071-021-01495-3
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic laws of brevity: conformity in Indri indri

Abstract: Vocal and gestural sequences of several primates have been found to conform to two general principles of information compression: the compensation between the duration of a construct and that of its components (Menzerath-Altmann law) and an inverse relationship between signal duration and its occurrence (Zipf's law of abbreviation). Even though Zipf's law of brevity has been proposed as a universal in animal communication, evidence on non-human primate vocal behavior conformity to linguistic laws is still deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 65 publications
6
23
0
Order By: Relevance
“…We have validated with unprecedented detail, by studying more than 36 000 infochemical interactions, that Zipf’s Law of brevity operates at interspecies infochemical communication. Those results are in line with precedent studies in language, and other communication systems [18,2022,5355], suggesting the universality of this linguistic law and the principle of compression, from which it derives. Nevertheless, we have found no evidence that Zipf’s Law of brevity holds in intraspecific chemical communication—pheromones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have validated with unprecedented detail, by studying more than 36 000 infochemical interactions, that Zipf’s Law of brevity operates at interspecies infochemical communication. Those results are in line with precedent studies in language, and other communication systems [18,2022,5355], suggesting the universality of this linguistic law and the principle of compression, from which it derives. Nevertheless, we have found no evidence that Zipf’s Law of brevity holds in intraspecific chemical communication—pheromones.…”
Section: Discussionsupporting
confidence: 91%
“…Those results are in line with precedent studies in language, and other communication systems [18,[20][21][22][53][54][55], suggesting the universality of this linguistic law and the principle of compression, from which it derives. Nevertheless, we have found no evidence that Zipf's Law of brevity holds in intraspecific chemical communication-pheromones.…”
Section: Discussionsupporting
confidence: 89%
“…We have shown that Menzerath's law, but not MAL, arises also for a simple memoryless source with three emitted symbols. This observation shows that the mere Menzerath's law is not a property that distinguishes complex systems, which makes necessary to review and revise some previous comparative studies in human and non-human communication [21][22][23][24][25][26][27][28] or in other fields including genomics or ecology [17,18,68]. Moreover, as we have shown analyzing the Standarized Gutenberg Corpus on 21 languages, beyond a certain length of words, the inverted regime is found indeed, providing new evidence for the applicability of MAL.…”
Section: Discussionmentioning
confidence: 59%
“…The memoryless source model reproduces the negative correlation between the size of the constituents and the size of the whole. Therefore, recent studies that have found Menzerath's law in the communication systems of some animal species and attributed it to a certain complexity of communication systems of these living beings [21][22][23][24][25][26][27][28] should be carefully reviewed. The memoryless source model considered in this paper is a baseline model operating in terms of grapheme classes but it could be easily generalized and extended to other types of constituents and substructures such as phonemes, sentences, or breath groups that are typical of speech.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation